Childhood trauma and fear of childbirth: findings from a birth cohort study - Porthan Elviira; Lindberg Matti; Härkönen Juho; Scheinin Noora M; Karlsson Linnea; Karlsson Hasse; Ekholm Eeva (SPRINGER WIEN, 2025)
The aim of this study is to investigate if experiencing childhood trauma (emotional abuse, emotional neglect, physical abuse, physical neglect, or sexual abuse) or a greater total burden of childhood trauma increase the risk of fear of childbirth (FOC). This study included 2556 women living in Southwest Finland. Women were recruited during routine ultrasound visits at gestational week (gwk) 12. Experiencing childhood trauma was assessed in retrospect with the Trauma and Distress Scale (TADS) questionnaire completed at gwk 14. Information on the diagnosis of FOC (ICD-10 diagnosis O99.80) was obtained from the Finnish Medical Birth Register. Associations between childhood trauma (domains and total TADS score) and FOC were analyzed with logistic regression in unadjusted and adjusted models. Emotional abuse (aOR 1.25, 95% CI 1.10-1.42), emotional neglect (aOR 1.26, 95% CI 1.08-1.46), and a greater total burden of trauma (TADS total score) (aOR 1.06, 95% CI 1.02-1.10) increased the risk for FOC. We found no evidence for physical abuse (aOR 1.15, 95% CI 1.00-1.32), physical neglect (aOR 1.06, 95% CI 0.92-1.22), and sexual abuse (aOR 1.24, 95% CI 0.99-1.56) associating with FOC. Childhood emotional abuse, emotional neglect, and a greater total burden of childhood trauma increase the risk for FOC. However, the childhood traumatic events were inquired in retrospect, which could distort the events.